2011
DOI: 10.1016/j.cmet.2011.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Small Nucleolar RNAs U32a, U33, and U35a Are Critical Mediators of Metabolic Stress

Abstract: SUMMARY Lipotoxicity is a metabolic stress response implicated in the pathogenesis of diabetes complications and has been shown to involve lipid-induced oxidative stress. To elucidate the molecular mechanisms of lipotoxicity, we used retroviral promoter trap mutagenesis to isolate a cell line that is resistant to lipotoxic and oxidative stress. We show that loss of three box C/D small nucleolar RNAs (snoRNAs) encoded in the ribosomal protein L13a (rpL13a) locus is sufficient to confer resistance to lipotoxic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
207
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(220 citation statements)
references
References 47 publications
4
207
0
1
Order By: Relevance
“…Our previous studies have shown that following exposure to lipotoxic conditions, snoRNAs from the rpL13a locus accumulate in the cytosol and function as essential mediators of cell death. 22 Based on the requirement of RNase activity for complementation, we hypothesized that the biochemical function of RNASET2 during lipotoxicity might contribute to the biogenesis of the rpL13a snoRNAs. To test this possibility, we compared RNASET2-deficient 2B1 and WT CHO cells for cytosolic accumulation of the rpL13a snoRNAs in response to palm treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies have shown that following exposure to lipotoxic conditions, snoRNAs from the rpL13a locus accumulate in the cytosol and function as essential mediators of cell death. 22 Based on the requirement of RNase activity for complementation, we hypothesized that the biochemical function of RNASET2 during lipotoxicity might contribute to the biogenesis of the rpL13a snoRNAs. To test this possibility, we compared RNASET2-deficient 2B1 and WT CHO cells for cytosolic accumulation of the rpL13a snoRNAs in response to palm treatment.…”
Section: Resultsmentioning
confidence: 99%
“…24,31 The observation that treatment of cells with more direct inducers of oxidative stress, such as hydrogen peroxide, also causes cytoplasmic snoRNA accumulation suggests that ROS may be an upstream signal for the redistribution of snoRNAs. 22 Because cells haploinsufficient for RNASET2 fail to accumulate the rpL13a snoRNAs in the cytoplasm, but have no apparent defect in the generation of these snoRNAs (that is, nuclear levels are unchanged), we tested whether haploinsufficiency of RNASET2 modulated the generation of ROS in response to palm. Following supplementation of the media with palm, we quantified cellular superoxide by dihydroethidium (DHE) staining, and cellular hydrogen peroxide by 2′, 7′-dichlorodihydrofluorescein diacetate (DCF) staining.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies suggest yet another function for snoRNAs, in particular, as signals of metabolic stress. Here we note that snoRNAs have been previously linked to lipotoxicity (25), and cells deficient in intronic snoRNAs are resistant to cell death induced by PA treatment (40).…”
Section: Discussionmentioning
confidence: 99%